ПРЕДУПРЕЖДЕНИЕ ВЫМОГАТЕЛЬСТВА (Journal of actual problems of jurisprudence, 2019)
An important role in the prevention of extortion is given to law enforcement agencies, as currently in their activities leading direction is theprevention of crime.In our view, prevention can meet the challenges of combating extortion most humane way with minimal cost to society,particularly without the inclusion of "full force" of the mechanism of criminal justice without the use of such an acute form of government coercion,such as criminal penalties.